ANALYSIS OF THE PHENOMENA OF THE MASS JUDGMENT FROM A LEGAL SOCIOLOGICAL POINT OF VIEW - Octavia Zulkarnain (HERMENEUTIKA : Jurnal Ilmu Hukum, 2023)
The act of taking the law into your own hands (eigenrichting) is a disgraceful act and also violates the laws in force in Indonesia. Vigilante is referred to from the Dutch language, namely "Eigenrechting" which means how to take the law by yourself, take rights without regard to the law, without being known by the government and without using the tools of government power. Facts on the ground show that there are vigilante acts that almost always occur at the same time as a number of other individual rights are violated. For this reason, the state prohibits vigilante action because it is contrary to applicable law. Taking the law into your own hands is also an indicator indicating a low level of legal awareness in society. This paper aims to provide an overview of vigilantism (Eigenrechting) and to explain the phenomenon of mass judgment from the perspective of the sociology of law. This study applies normative legal research using approaches that include the Case Approach, Legislation Approach and Legal Concept Analysis Approach. Based on the analysis carried out, it can be seen that vigilante acts are triggered by emotional factors towards law enforcers and suspected criminals. On the other hand, perpetrators of taking the law into their own hands can be subject to criminal penalties in accordance with Article 351 of the Criminal Code and Article 261 of Law no. 1 of 2023. The act of taking the law into your own hands according to the national legal order violates the principle of the presumption of innocence so that a determination regarding whether an individual is guilty or not must go through a legal process first, this is because there is a chance that he is not guilty but becomes a victim of taking the law into his own hands.